Loss of protein targeting to glycogen sensitizes human hepatocellular carcinoma cells towards glucose deprivation mediated oxidative stress and cell death. Issue 3 (11th June 2015) - Yang, Rongqiang; Zhang, Mei; Gustafson, Amber Renee; Wang, Eugenia; Cole, Marsha Paulette; Tooley, Christine Elizabeth Schaner; Cheng, Alan
Abstract : PTG is a protein that is critical for glycogen accumulation in various tissues such as the liver. Our present study shows that its loss sensitizes liver cancer cells towards metabolic and oxidative stress. Abstract : Protein targeting to glycogen (PTG) is a ubiquitously expressed scaffolding protein that critically regulates glycogen levels in many tissues, including the liver, muscle and brain. However, its importance in transformed cells has yet to be explored in detail. Since recent studies have demonstrated an important role for glycogen metabolism in cancer cells, we decided to assess the effect of PTG levels on the ability of human hepatocellular carcinoma (HepG2) cells to respond to metabolic stress. Although PTG expression did not significantly affect the proliferation of HepG2 cells under normal culture conditions, we determined that PTG plays an important role during glucose deprivation. Overexpression of PTG protected cells from cell death in the absence of glucose, whereas knocking down PTG further promoted cytotoxicity, as measured by the release of lactate dehydrogenase (LDH) into the media. Additionally, we demonstrated that PTG attenuates glucose deprivation induced haeme oxygenase-1 (HO-1) expression, suggesting that PTG protects against glucose deprivation-induced oxidative stress. Indeed, treating cells with the antioxidant N -acetyl cysteine (NAC) rescued cells from cytotoxicity caused by glucose deprivation. Finally, we showed that loss of PTG resulted in enhanced autophagy. In control cells, glucose deprivation suppressed autophagy as determined by the increase in the levels of p62, an autophagy substrate. However, in knockdown cells, this suppression was relieved. Blockade of autophagy also attenuated cytotoxicity from glucose deprivation in PTG knockdown cells. Taken together, our findings identify a novel role for PTG in protecting hepatocellular carcinoma cells from metabolic stress, in part by regulating oxidative stress and autophagy.